Effect of royal jelly on male infertility - E. Al-Sanafi, Ali; A. Mohssin, Safaa; Abdullah Al-Mahmood, Sinan Mohammed (Thi-Qar University, 2007)
Male infertility may occur due to different causes, therefore , different therapeutic approaches have been applied in order to improve the ability of men to get children . Semen analysis is used to determine the fertility potential in males, but the occurrence of pregnancy is the evidence of sperm ability for fertilization. Although male fertility is affected by food and nutrients, but little attention is paid for the use of Royal Jelly and no previous studies on the use of Royal Jelly in the treatment of male infertility. Eighty – three infertile men were treated with Royal Jelly, twenty – two with 100mg Royal Jelly, twenty –one with 50mg Royal Jelly, twenty with 25mg Royal Jelly and twenty with pure honey. Our study showed that, the treatments were safe and there were no side effects. After three months of treatment , the sperm active motility , testosterone level , Lutelizing hormones level , sluggishly motile sperm and intercourse / week increased significantly in infertile men treated with Royal Jelly , while sperm count and FSH level increased not significantly . On the basis of results, Royal Jelly is safe and effective in the treatment of male infertility.